Effects of 8-Week Complex Balance Training in Young Alpine Skiers: A Pilot Study - Słomka, Kajetan J. (Biomed Res Int, 2018)
OBJECTIVES: The purpose of this study was to determine the effects of an 8-week complex balance training program on dynamic balance in skiers according to the new balance training protocol. DESIGN: Intervention study, comprising 8 weeks of core stability, plyometric, balance, and stretching exercises. PARTICIPANTS: Ten young skiers volunteered to take part in this study (average age, height, and body mass were 16,44 +/- 1,07 years, 172,76+/-8,84 cm, and 67,4 11,44 kg, respectively (mean +/- SD)). MAIN OUTCOME MEASURES: Subjects' dynamic balance performance was assessed and retested after training completion with the use of dynamic balance measurement within the Optojump Next System. RESULTS: The results of 8-week complex balance training showed significant improvements for jump height (H) and flight time (FT) for the left leg and jumping area in both legs. CONCLUSION: The complex balance training program improved parameters of dynamic stability in young skiers and led to decreased asymmetry between lower extremities.